HUBUNGAN KARAKTERISTIK SISWA DAN ORANGTUA DENGAN STATUS GIZI SISWA SEKOLAH DASAR NEGERI KB 4 KOTA BANJARMASIN - Mahdayani Lesda; Mochamad Rachmat; Sutanto Priyo Hastono (Persagi, 2006)
Background: Several studies showed that among students at elementary school, undernutrition and overnulrition are still a nutrition problem. It was reported that undernutrilion among school students is 35% and 25% for male and female, respectively. However, the prevalence of overnulrition is 9% and 11% for male and female respectively. Objective: To analyze the association between student characteristics, parent characteristics, and nutritional status of student at public elementary school, namely KB4 in Banjarmasin city. Methods: The school was chosen because it was a pilot school in this city. Students selected purposively in grade IV, V, and VI so that the total of students was 190. The nutritional status assessed and catagorized using WAZ of WHO-NCHS standard. Results: The study indicated that prevalence of undeiweight was 20.5%. There was a significant association between nutrition status and having daily breakfast, mother's educational level, mother's nutrition knowledge, and parent's income. While purchase food at school jajan, student's nutrition knowledge, tafher's education level, mother's occupation status, and total member in family were not associated significantly with student